Pemaknaan Struktur Penalaran Moral Anak pada Hikayat Kalilah dan Dimnah - Abda Billah Faza Muhammadkan Bastian; Dind Ibra Benign Sajid; Rina Febriana (Universitas Cokroaminoto Yogyakarta, 2026)
This study aims to map the structure of moral reasoning contained in the Hikayat Kalilah and Dimnah through Lawrence Kohlberg's moral development theory. The method used is qualitative with a literature study approach and content analysis techniques on the text of the saga. The results of the study indicate that the main moral values ​​in the saga are honesty, compassion, friendship, and hard work, which are represented through Kohlberg's three stages of moral reasoning: punishment-obedience orientation, relativist-instrumental orientation, and